The photochemistry of rhenium(I) tricarbonyl N-heterocyclic carbene complexes - Vaughan, J.; Reid, Brodie; Ramchandani, S.; Wright, Phillip; Muzzioli, S.; Skelton, B.; Raiteri, Paolo; Brown, David; Stagni, S.; Massi, Massimiliano (Royal Society of Chemistry, 2013)
The photophysical and photochemical properties of the new tricarbonyl rhenium(I) complexes bound to N-heterocyclic carbene ligands (NHC), fac-[Re(CO)3(N^C)X] (N^C = 1-phenyl-3-(2-pyridyl)imidazole or 1-quinolinyl-3-(2-pyridyl)imidazole; X = Cl or Br), are reported. The photophysics of these complexes highlight phosphorescent emission from triplet metal-to-ligand (3MLCT) excited states, typical of tricarbonyl rhenium(I) complexes, with the pyridyl-bound species displaying a ten-fold shorter excited state lifetime. On the other hand, these pyridyl-bound species display solvent-dependent photochemical CO dissociation following what appear to be two different mechanisms, with a key step being the formation of cationic tricarbonyl solvato-complexes, being themselves photochemically active. The photochemical mechanisms are illustrated with a combination of NMR, IR, UV-Vis, emission and X-ray structural characterization techniques, clearly demonstrating that the presence of the NHC ligand is responsible for the previously unobserved photochemical behavior in other photoactive tricarbonyl rhenium(I) species. The complexes bound to the quinolinyl-NHC ligand (which possess a lower-energy 3MLCT) are photostable, suggesting that the photoreactive excited state is not any longer thermally accessible. The photochemistry of the pyridyl complexes was investigated in acetonitrile solutions and also in the presence of triethylphosphite, showing a competing and bifurcated photoreactivity promoted by the trans effect of both the NHC and phosphite ligands.